Elastic electron scattering using the finite element method: Forward and inverse problems - Aubry, Denis; Lenaig Hamon, Ann-; Puel, Guillaume (European Journal of Computational Mechanics, 2010)
We address here the case of electron-matter elastic interaction as it occurs in Transmission Electron Microscopy (TEM) experiments. In the forward problem, we show that it is possible to derive the scattered electron wave function as the solution of a Helmholtz equation. This equation depends on the spatial potential associated with the analyzed sample, and can be relevantly solved using the Finite Element Method (FEM). Then we present an inverse formulation dealing with the determination of the sample’s potential when the total wave function is measured at the exit plane of the sample.